Consults for conflict: the history of ethics consultation - Tapper, Elliot B. (Baylor Health Care System, 2013)
The very existence of ethics consultation reflects both the increasing complexity of modern medicine's ethical questions and our discomfort with the prospect of answering them alone. Two developments in the past century were instrumental in driving the development of ethics consultation—organ replacement therapy and intensive care. With the proliferation of extreme life-prolonging measures came the thorny difficulties in the withdrawal of such services or rationing when resources were poor. Insofar as “someone must,” lamented Dr. Karen Teel (a pioneer of ethics consultation), the physician “is charged with the responsibility of making ethical judgments which we are sometimes ill-equipped to make.” More than anything, ethics consultation has come to best satisfy a central desire of American health care—sharing the responsibility for tough decisions.